Overlooking cancer: Practising cancer diagnostics in the subjunctive mood - Frumer, Michal (Tidsskrift for Forskning i Sygdom og Samfund, 2018)
The paper explores the management of uncertainty, when watching the possible development of signs of lung cancer at a lung cancer outpatient clinic. Based on ethnographic fieldwork at a clinic in Denmark, it is presented how potential signs of lung cancer, termed nodules, on people’s lungs call to be managed due to the hope and aspirations of alleviating cancer and cancer related suffering. The paper suggests that the significance of the uncertainties of lung nodules is tried out by watching the nodule with follow-up CT-scans and opposed by focusing on intervention. Approaching the management of uncertainties as in a subjunctive mood, the paper proposes that the physicians try out a possible but indeterminate future of cancer, to contain the prognostic horizon and uncertainties by acting ‘as if’ cancer will develop. However, in this cautionary managing of cancer doubt and uncertainty, ambiguities are (re-)produced, leaving an interim certainty: This lung nodule is most likely not and may never become cancer.